Assess Nurses’ Knowledge and Practice In Relation to Infection Prevention and Related Factors at Saudi Arabia, 2024 - Nedaa Mohammed Ali Alromaili; Mohammed Abdullah Almohaimeed; Hussah Saad Albrahim; SajdiInad D Alotaibi; Helail Sulaiman Alotaibi; Reem Omar Alanezi; Muneefa Menwer Aldhafeeri; May Saad Almowans; Iman Nasser Sanad Alanazi; Jawharah Sunaid Alsenaid‏; Dhuwayhi Qaed Dhuwayhi Alotaibi (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Nursesare front line of protecting themselves and patients from infection.Hospital-acquired infections (HAIs) contribute to increased length of hospital stay, higher mortality and higher health-care costs. Infection, prevention, and control (IPC) practices are essential to protect patients and staff within healthcare facilities. HCPs play a pivotal role in preventing these infections through their knowledge and compliance to infection control practices. The study aimed: To Assess nurses’ knowledge and practice in relation to infection prevention and related factors. Materials and Methods:A cross-sectional study was conductedat hospital in Makkah, Saudi Arabia from January to March2024. A convenience sample from nurses of 219 participated in thepresent study. A structured self-administered questionnaire was used to collect data. A Multivariable logistic regression model was fitted to identify factors associated with the knowledge and practice of HCPs regarding infection prevention. Result: This study displays that the overall knowledge and practice of nurses regarding infection prevention are 59.4% (95% CI: 53.0–65.8) and 53% (95% CI: 46.6–59.4), respectively. Educational level of diploma [AOR: 0.8, 95% CI: 0.67–0.83], years of work experience ≤ 10 [AOR: 1.7, 95% CI: 1.3–9.28], and being trained in infection prevention [AOR: 2.5 (2.3–8.0)] were found to be factors that affect the knowledge of nurses about infection prevention. Moreover, ≤ 10 years of work experience [AOR = 1.5, 95% CI: 1.2–10.1] and being trained in infection prevention [AOR = 2.2, 95% CI: 1.94–13.5] were found to be factors that affect the practice of nurses regarding infection prevention. Conclusions:The majority of nurses was competent and followed best practices. Nonetheless, a sizable fraction of nurses lacked sufficient infection prevention training and expertise. Years of work experience and the level of infection prevention training were linked to the nurses' knowledge and practice. Furthermore, another predictor of HCP expertise was their educational background. As a result, hospital healthcare personnel should follow the national infection prevention guidelines. Nurses should receive infection prevention training from the policy designers to advance their understanding and proficiency in this field.